PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Yogi Isnanto; Suharno Suharno; Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The purpose of this study was to determine the effect of clarity of budget targets, accounting controls and reporting systems on the accountability of the performance of government agencies. This type of research was a survey of SKPD employees in Sukoharjo Regency. The sample of this study was 51 respondents consisting of the Head of Service, Head of Finance and Secretary. Data collection techniques using questionnaires and literature study. Data analysis techniques used are descriptive analysis, test instruments, test classic assumptions and test hypotheses. The results of this study indicate that the clarity of budget targets, accounting controls and reporting systems positive significantly influences the performance accountability of government agencies in Sukoharjo Regency.